CAST-IRONS AT HIGH TEMPERATURES - A. N. Krutilin; R. L. Topfenets; M. Ju. Lendneva (Литьë и металлургия)
The results of investigations of physical-mechanical characteristics of cast iron slugs, received by semicontinuos way of casting, at temperatures from 850 up to 1100^ С are given.